Identification of Slc6a19os and SOX11 as Two Novel Essential Genes in Neuropathic Pain Using Integrated Bioinformatic Analysis and Experimental Verification - Chen, Peng; Wang, Chen; Lin, Dongsheng; Li, Bing; Ye, Shuai; Qu, Jinglian; Wang, Wenjing (Frontiers in Neuroscience, 2021)
The aim of this study was to identify critical genes associated with neuropathic pain. We also used the ceRNA hypothesis to identify related lncRNAs and miRNAs with potential regulatory roles. We downloaded GSE107180 from the Gene Expression Omnibus database, screened differentially expressed genes (DEGs) using R software, performed comprehensive bioinformatic analyses, and validated the expression of lncRNA Slc6a19os, miR-125a-5p, miR-125b-5p, miR-351-5p, and Sox11 by qRT-PCR and Western blots. We identified 620 DEGs in spared nerve injury (SNI) mice compared with sham (control) mice, including 309 mRNAs and 311 non-coding RNAs. The up-regulated mRNAs were enriched primarily in several inflammation-related GO biological processes and KEGG signaling pathways. A ceRNA network was constructed that included 82 mRNAs, four miRNAs, and two lnRNAs. An IPA-based interaction network for mRNAs differentially expressed in the ceRNA identified several biological processes, including “cellular development, connective tissue development and function, tissue development”. Compared with sham mice, lncRNA Slc6a19os and Sox11 expression were significantly up-regulated in dorsal root ganglion (DRG) samples from SNI mice based on qRT-PCR and Western blots (P<0.05). MiR-125a-5p, miR-125b-5p, and miR-351-5p expression were down-regulated in DRG samples from SNI mice based on qRT-PCR (P<0.05). We concluded that Sox11 and lncRNA Slc6a19os were novel essential genes in the pathogenesis and progression of neuropathic pain and speculated that these two genes were regulated by miR-125a-5p, miR-125b-5p, and miR-351-5p.